Penegakan Hukum terhadap Pelaku Tindak Pidana Persetubuhan yang Dilakukan oleh Anak (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
Law enforcement against perpetrators of sexual intercourse committed by children is a complex issue that requires a balance between aspects of justice, protection, and rehabilitation. Children as perpetrators of criminal acts are in a unique position because of their status as legally and psychologically immature individuals. This study aims to analyze the law enforcement process against children involved in sexual intercourse, including the application of sanctions that are in line with the principles of restorative justice and the protection of children's rights. The research method used is normative juridical with a legal approach and case studies. The results of the study show that the juvenile criminal justice system in Indonesia refers to Law Number 11 of 2012 concerning the Juvenile Criminal Justice System, which emphasizes a diversion approach and non-criminal efforts in resolving children's cases. However, there are obstacles in implementation due to limited resources, understanding of law enforcement, and social stigma attached to child perpetrators. This study recommends increasing training for law enforcement, strengthening psychological assistance mechanisms, and developing comprehensive rehabilitation programs. Thus, law enforcement against children who commit sexual intercourse crimes must consider the balance between strict law enforcement and the protection of children's rights, so that the goals of social reintegration and rehabilitation can be achieved optimally.